2016
DOI: 10.1016/j.ctim.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Spiritist “passe” energy therapy in reducing anxiety in volunteers: A randomized controlled trial

Abstract: NCT02376959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…No adverse effects were verified with the application of this energy therapy by "passe" in preoperative hospitalized patients investigated. These results are consistent with studies that assess the effects of the SP (de Souza Cavalcante et al 2016;Carneiro et al 2016Carneiro et al , 2017Carneiro et al , 2018a.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No adverse effects were verified with the application of this energy therapy by "passe" in preoperative hospitalized patients investigated. These results are consistent with studies that assess the effects of the SP (de Souza Cavalcante et al 2016;Carneiro et al 2016Carneiro et al , 2017Carneiro et al , 2018a.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have evaluated SP biofield therapy and have shown evidence in reducing anxiety (de Souza Cavalcante et al 2016;Carneiro et al 2016Carneiro et al , 2017 and muscle tension (Carneiro et al 2016(Carneiro et al , 2017, in addition to increasing immune response (elevation of the count of lymphocytes) (Carneiro et al 2016) and wellbeing (Carneiro et al 2016(Carneiro et al , 2017. However, studies are lacking evaluation of the effects of this therapy on preoperative anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that with the appropriate training in Spirituality/Religiosity, the main obstacles pointed out by physicians to take a patient's spiritual history can be overcome. Training should lead them to: (1) acquire a more positive attitude toward the importance attributed to the spiritual approach in clinical practice; (2) have a better understanding of the role of Spirituality in Health; (3) know the foundations of the main religious traditions in order to acquire subsidies to respect patients' beliefs and understand their spiritual needs; (4) develop spiritual care skills to care for patients from different cultures and different spiritual and religious contexts; (5) acquire knowledge on the philosophy of care; (6) be sensitized to a patient's spiritual and cultural needs; (7) recognize a patient's spiritual suffering and promote comprehensive care; (8) be naturally receptive and safe to support and encourage patients' religious beliefs; (9) learn that more than 3,300 scientific studies on Spirituality/Religiosity and Health have proven that religious activities and beliefs are related to better physical and mental health, and quality of life in the most different aspects; (10) explore the relevant instruments published in the literature that guide the taking of a patient's spiritual history; (11) take the spiritual history during the anamnesis, preferably at the end of social history; (12) practice doing spiritual anamnesis a few times to be able to carry it out in a few minutes; (13) become aware of their own finitude, and understand death as a natural process of life (Chibnall and Duckro, 2000;Chibnall et al, 2002;Graves et al, 2002;Sandor et al, 2006;Anandarajah and Mitchell, 2007;Feldstein et al, 2008;Culliford, 2009;Lucchetti et al, , 2013aLucchetti et al, , 2015Koenig, 2012aKoenig, ,b, 2015Koenig et al, 2012;Kübler-Ross, 2012;Talley and Magie, 2014;Arantes, 2016;Cavalcante et al, 2016;Peres et al, 2018;Puchalski et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Energy therapy is a form of complementary medicine that aims to create a state of balance through energy flow in the human body. Energy therapy heals certain mental or physical disorders by rebalancing the energy field, reduces stress and anxiety, and promotes wellbeing [18].…”
Section: Entropymentioning
confidence: 99%